The effect of processing fluency on semantic illusion - Yallak, Ece. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Semantic illusion occurs when a question like “How many animals of each kind did Moses take on the ark?” was responded with “two” in spite of knowing that animals were taken to the ark by “Noah” not “Moses”, according to the flood myth. The aim of the present study is to investigate the effect of different types of processing disfluencies on semantic illusion rate and to see whether there is a correlation between confidence in knowledge and illusion rate. Previous research by Song and Schwarz (2008) showed that disfluent processing facilitates detection of illusions. On the other hand, Geipel, Hadjichristidis, and Surian’s (2015) findings showed the opposite pattern. With the aim to clarify this incompatibility in earlier findings, we conducted two experiments, in which the effects of conceptual and perceptual (dis)fluencies on semantic illusion rate were investigated. Results of the first experiment supported Geipel et al.’s (2015) finding by showing less illusion in native language (i.e., fluent) compared to the foreign language (i.e., disfluent). On the other hand, perceptual fluency did not influence illusion rate. Additionally, confidence in knowledge was revealed to be negatively correlated with illusion rate, and positively correlated with correct response rate in undistorted questions.
Keywords: Semantics (Philosophy); Semantics -- Methodology.